Recognising moulting behaviour in trilobites by examining morphology, development, and preservation: Comment on Błażejowski et al. 2015 - Drage, H; Daley, A (Wiley, 2016)
A 365 million year-old trilobite moult-carcass assemblage was described by Błażejowski et al. (2015) as the oldest direct evidence of moulting in the arthropod fossil record. Unfortunately, their suppositions are insufficiently supported by the data provided. Instead, the morphology, configuration, and preservational context of the highly fossiliferous locality (Kowala Quarry, Poland) suggest that the specimen consists of two overlapping, queued carcasses. The wider fossil record of moulting actually extends back 520 million years, providing an unparalleled opportunity to study behaviour, ecology, and development in early animals. Taking cues from modern analogues, it is possible to quantify precise details about moulting behaviour to determine broad-scale evolutionary trends, ontogenetic sequences, and morphological selection pressures. In this review, we argue that this rich source of data has been underused in evolutionary studies, though has great potential for investigating the life history and evolution of arthropods in deep time.